Analysis of the effect of SBI interest rates, world oil prices, world gold prices, and the Straits Time Index on the Composite Stock Price Index (IHSG) on the Indonesian Stock Exchange for the period January 2005-May 2010 - Nimas Ayu Anindya Kirana (Institute of Accounting Research and Novation (IARN), 2021)
The Jakarta Composite Index (JCI) is an index that can be used to represent the situation of the Indonesian stock market. The movement of JCI can be caused by regional stock exchanges and macroeconomic conditions such as interest rates, energy prices, etc. The increase in JCI showed the market has a bullish condition, conversely a decrease in JCI would show the bearish condition. This study was intended to know and analyze the effect of SBI interest rates, Oil prices, Gold prices and the Straits Time Index (STI) which represents the Singapore stock market. The method used in this study is multiple linear regression analysis, T test, F test at a significance level of 5 % and performed with Statistical Package for Social Science (SPSS) version 17.0. This research focused on January 2005 until May 2010, using a monthly data. The results of this study showed that the SBI interest rate, Gold prices, and STI significantly affect the Jakarta Composite Index, while oil prices do not significantly affect the JCI. The SBI interest rate has a negative influence on JCI and the other variables (gold price and STI) have a positive influence on JCI.